Coast line searched by the western division of Sledges from Northumberland Sound under Commr. Richards and track of H. M. Sledge "John Barrow," Commr. Sherard Osborn, H. M. S. "Pioneer" / Day & Son Lithrs to the Queen (Hydrographic Office of the Admiralty, 1855)
Color;